1998
DOI: 10.1034/j.1399-3054.1998.1020406.x
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous gibberellin A1 levels control thermoperiodic stem elongation in Pisum sativum

Abstract: Gibberellin (GA) is believed to be involved in thermoperiodic stem elongation. With this in mind, we studied the correlation between gibberellin A1 (GA1) levels and stem elongation affected by alternating day (DT) and night temperature (NT) in 5 genotypes of Pisum sativum differing in their degree of dwarfism. The endogenous GA content in the tissue of two of the genotypes was determined by combined gas chromatography and mass spectrometry. The wild genotype developed 40 to 50% shorter stems and internodes und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
41
3

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 0 publications
5
41
3
Order By: Relevance
“…The enhanced inhibition of internode elongation correlated with a marked reduction in GA1 levels in these seedlings suggesting that regulation of GA biosynthesis is a major control point for this response. Further analysis showed that pea plants dwarfed by paclobutrazol had a higher rate of 2β-hydroxylation of GA1, leading to lower levels of endogenous GA1 and shorter stems and internodes under negative DIF (Grindal, 1998a). Together these results indicate that, for pea at least, thermoperiodic responses are mediated by changes in the endogenous levels of GA1, via GA biosynthetic and inactivation steps.…”
Section: Diurnal Temperature Effectsmentioning
confidence: 66%
See 2 more Smart Citations
“…The enhanced inhibition of internode elongation correlated with a marked reduction in GA1 levels in these seedlings suggesting that regulation of GA biosynthesis is a major control point for this response. Further analysis showed that pea plants dwarfed by paclobutrazol had a higher rate of 2β-hydroxylation of GA1, leading to lower levels of endogenous GA1 and shorter stems and internodes under negative DIF (Grindal, 1998a). Together these results indicate that, for pea at least, thermoperiodic responses are mediated by changes in the endogenous levels of GA1, via GA biosynthetic and inactivation steps.…”
Section: Diurnal Temperature Effectsmentioning
confidence: 66%
“…Particularly in the horticultural industry, plant morphology is routinely manipulated by altering day length (photoperiod) and temperature of the growth conditions. Plant development can also be influenced by the topical application of hormones, for example, GA, is known to control stem elongation and is often applied to control crop morphology (Grindal et al, 1998a). However, as chemical applications are becoming increasingly less acceptable for use in a commercial environment, thermoperiodic manipulation, i.e.…”
Section: Diurnal Temperature Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jensen et al (1996) reported higher levels of GA 1 in Campanula isophylla grown under positive DIF than negative DIF. It has been suggested that altered stem elongation of pea (Pisum sativum) plants in response to diurnal temperature alternations may be mediated by changes in the endogenous levels of GA 1 (Grindal et al, 1998a). GA 1 levels were found reduced by almost 60% under a temperature regime with low DT and high NT compared to a temperature regime with high DT and 1 This work was supported by the Norwegian Research Council (grant no.…”
mentioning
confidence: 99%
“…GA 1 levels were found reduced by almost 60% under a temperature regime with low DT and high NT compared to a temperature regime with high DT and low NT, with both temperature treatments having the same daily average temperature. The study of GA metabolites suggested that thermoperiodicity could affect both biosynthesis and inactivation steps of GA 1 (Grindal et al, 1998a). Furthermore, based on experiments with GA biosynthesis inhibitors and applications of GA 1 and GA 3 (GA 3 is protected from deactivation by enzymatic 2-oxidation), it has been hypothesized that reduced GA 1 levels in stem tissue under negative DIF are caused by enhanced inactivation of GA 1 by 2-oxidation in pea (Grindal et al, 1998b).…”
mentioning
confidence: 99%